白令海峡水团来源的镭同位素示踪 - 陈敏; 李艳平; 邱雨生; 杨俊鸿 (2011)
对白令海峡64.3°n纬向断面镭同位素的研究表明,水体中226rA比活度2、28rA比活度和228rA/226rA)A.r.存在明显的纬向变化,反映出太平洋与北冰洋水体交换的多种路径。根据温度、盐度和镭同位素的水平与垂直分布,太平洋水进入北冰洋的路径可能主要有3支,分别为白令海峡西侧的阿拉德水、白令海峡东侧的阿拉斯加沿岸水和中部的白令海陆架水。2003年7月和9月对该断面西侧站位进行的复测显示,水体中的226rA比活度2、28rA比活度和228rA/226rA)A.r.发生了明显变化,9月份测值均高于7月份测值,说明白令海峡西部水体在9月份可能受到西伯利亚沿岸流南向混合的影响。 Radium isotopes in the water column along 64.3°N in the Bering Strait were determined to reveal the northward flow of the Pacific water.The specific activities of 226Ra and 228Ra,and the 228Ra/226Ra)A.R.show a longitudinal variation in the Bering Strait,depicting the pathways of Pacific inflow.Based on the distributions of temperature,salinity and radium isotopes in the Bering Strait,three water masses were identified: the Anadyr Water in the western channel,the Alaskan Coastal Water in the eastern channel,and the Bering Shelf Water in the central strait.A subseasonal variation of radium isotopes in the Bering Strait was observed.The specific activities of 226Ra and 228Ra,and 228Ra/226Ra)A.R.in September are higher than those observed in July,indicating water in the western Bering Strait is influenced by the southward flow of the Siberia Coastal Current in September. 国际极地年中国行动计划项目;中国第3次北极科学考察资助项目;福建省自然科学基金杰出青年基金项目(2009J06026)